1988
DOI: 10.1128/mcb.8.11.4840
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transcriptional regulation by phytochrome of the genes for phytochrome and chlorophyll a/b-binding protein in Avena sativa.

Abstract: We have examined phytochrome-regulated transcription of phytochrome (phy) and chlorophyll a/b binding protein (cab) genes in dark-grown Avena seedlings by using run-on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 68 publications
(77 reference statements)
1
113
1
1
Order By: Relevance
“…This low amount of Pfr may be achieved with only very low fluences of either red or far red light. Furthermore, this regulation results in an observed decrease in the abundance of phytochrome message due, at least in part, to a reduction in transcriptional activity (13). The response has been observed in maize seedlings (2), although to a lesser extent than seen in other species, such as oat (3), rice (10), and pea (26), and to a greater extent than in zucchini (12).…”
mentioning
confidence: 94%
“…This low amount of Pfr may be achieved with only very low fluences of either red or far red light. Furthermore, this regulation results in an observed decrease in the abundance of phytochrome message due, at least in part, to a reduction in transcriptional activity (13). The response has been observed in maize seedlings (2), although to a lesser extent than seen in other species, such as oat (3), rice (10), and pea (26), and to a greater extent than in zucchini (12).…”
mentioning
confidence: 94%
“…It has been shown that phytochrome depresses transcription of its own gene, phyA (Lissemore and Quail, 1988;Bruce and Quail, 1990;Dehesh et al, 1990;Bruce et al, 1991), and also the transcription of porA, the gene encoding POR (Batschauer and Apel, 1984;Mosinger et al, 1985). As a result of illumination, the inherently unstable phyA and porA mRNAs rapidly decline Colbert et al, 1985;Colbert, 1988).…”
Section: Morphological Cellular and Molecular Events During The Ligmentioning
confidence: 99%
“…PHYA mRNA is inherently unstable, with an apparent half-life of 4 hr (Seeley et al, 1992). In 4-day-old dark-grown oat seedlings, the rate of PHYA transcription is high, producing an abundant mRNA (Lissemore and Quail, 1988). Within minutes after a red light pulse, transcription of the PHYA gene stops and is followed by a rapid decrease in PHYA mRNA levels as a result of the short half-life of the PHYA mRNA.…”
Section: Introductionmentioning
confidence: 99%